PENGARUH MODEL PEMBELAJARAN PROJECT BASED LEARNING (PjBL) TERHADAP HASIL BELAJAR PESERTA DIDIK PADA MATA PELAJARAN PENDIDIKAN PANCASILA KELAS V DI SD NEGERI 146 KESSI KECAMATAN SINJAI TENGAH KABUPATEN SINJAI - Musdalifa; Sam’un Mukraimin; Musdalifah Syahrir (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study aims to determine the effect of the Project Based Learning (PjBL) learning model on the learning outcomes of fifth-grade students in the Pancasila Education subject at SD Negeri 145 Kessi, Sinjai Tengah District, Sinjai Regency. The research method used is quantitative with a quasi-experimental design of the nonequivalent control group design. The population in this study were all fifth-grade students of SD Negeri 145 Kessi. The research sample consisted of two classes, namely the experimental class taught using the PjBL model and the control class taught using conventional methods. The research instrument was a learning outcome test whose validity and reliability had been tested. Data were analyzed using an independent t-test. The results showed that there was a significant difference between the learning outcomes of students taught using the PjBL model and students taught using conventional methods (p < 0.05). The average learning outcomes of students in the experimental class were higher than those in the control class. Thus, it can be concluded that the Project Based Learning (PjBL) model has a positive effect on the learning outcomes of fifth-grade students in Elementary School 145 Kessi, Sinjai Tengah District, Sinjai Regency. This study recommends the implementation of the PjBL model as an innovative learning alternative to improve the quality of Pancasila Education learning in elementary schools.